Imagined past, present and futures in Murray–Darling Basin communities. (3rd May 2016) - Pearson, Leonie J.; Wilson, Samuel; Kashima, Yoshihisa; Lusher, Dean; Pearson, Craig J.
ABSTRACT: Over the past three decades, irrigation-dependent rural communities in Australia's Murray–Darling Basin have experienced profound economic, social and environmental changes, which they are attempting to accommodate through local government policy. As a contribution to participatory policy design research, in consultation with local governments we carried out focus groups to explore diversity of individuals' imagined past and present in two rural communities. This was followed by group development of a diverse range of future scenarios and agreement to three likely scenarios. The research identified presence or absence of three underlying themes – irrigation, innovation and inflow of people – that plausibly drive change in these rural communities. These themes are likely to be common to many rural communities that have depended on irrigated agriculture. They provide an example of participatory policy-making, as distinct from the historically employed top-down policy development that has occurred in the Murray–Darling Basin. Because of the diversity of perceptions of past, present and futures, and the ultimate adoption of business-as-usual within the final local government plans, the research emphasises the need to put effort into community deliberations to build cohesion and share ownership of the process for delivering locally nuanced community policy.